Research on the Chlorine Removal and Upgrading of Waste Plastic Pyrolysis Oil Using Iron-Based Adsorbents - Hyo Sik Kim; Hyun-Ji Kim; Jihyeon Kim; Jin-Ho Kim; Tae-Jin Kang; Suk-Hwan Kang; Yeji Lee; Soo Chool Lee; Chi-Seong Chang; Jong Wook Bae (Energies, 2025)
The emergence of plastics as an essential item in modern society has led to the problem of accumulating plastic waste. Accordingly, research is being conducted around the world to reduce the production of new plastics and develop technologies to recycle waste plastics. Among the existing waste plastic recycling technologies, oil production is possible through pyrolysis, but the pyrolysis oil produced in this way has a wide carbon range (more than C5–C25), and a very high olefin content (the presence of aromatic compounds), and the resulting high calorific value of pyrolysis oil is limited in its application range. In the case of oil obtained by pyrolyzing waste plastic containing Cl, there is a concern about corrosion in the reactor. Accordingly, it is possible to diversify the range of use of pyrolysis oil produced by suppressing corrosion through Cl removal as well as oil upgrading through cracking. Therefore, this study used red mud mixed with a series of adsorbents for Cl removal and pyrolysis oil upgrade. The adsorbent was physically mixed with a binder (kaolin or methylcellulose) and activated carbon, and the results before and after the reaction were confirmed through basic characteristic analysis.